Supraphysiologic Testosterone Administration Impairs Late Osseointegration in Male Rats - Goncalves, Vinicius de Paiva; Pinotti, Felipe Eduardo [UNESP]; Spolidorio, Luis Carlos [UNESP]; Marcantonio Jr, Elcio [UNESP]; Oliveira, Guilherme Jose Pimentel Lopes de; Steffens, Joao Paulo (Quintessence Publishing Co Inc, 2024)
Purpose: To evaluate the effect of supraphysiologic administration of testosterone in an early and late model of implant osseointegration in rat tibiae. Materials and Methods: A total of 40 rats were randomly allocated into four groups (n = 10/ group), which were divided according to the type of experiment and time of osseointegration: (1) vehicle (14 days), (2) testosterone (14days), (3) vehicle (42 days), and (4)testosterone (42 days). Testosterone cypionate (7.5 mg/kg) administration started 4 weeks before implant placement, and the injections were performed daily until euthanasia. Machined -surface titanium implants (2.2 mm in diameter and 4 mm high) were placed bilaterally in the tibia of animals 28 days after the first testosterone injection. At days 14 and 42 after implant placement, euthanasia was performed and the tibiae were harvested to perform biomechanical evaluation and histomorphometric analysis of bone -to -implant contact (BIC%) and bone between the threads (BBT%). Results: There was no statistical difference in the removal torque of the implants between the groups treated with the vehicle (control group) or testosterone (P > .05). At 14 days of osseointegration, the BIC% and BBT% did not differ between vehicle or testosterone groups (P> .05), while at 42 days, both the BIC% and BBT% were significantly reduced by testosterone compared to the vehicle group (P < .05). Conclusions: Testosterone cypionate in supraphysiologic dose impaired late -phase osseointegration in rat tibiae. . Int J Oral Maxillofac Implants 2024;39:50-56.
Keywords: androgens; testosterone; dental implants; osseointegration